2016
DOI: 10.1161/circoutcomes.115.002184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Optimism and Gratitude on Physical Activity, Biomarkers, and Readmissions After an Acute Coronary Syndrome

Abstract: Background Positive psychological constructs, such as optimism, are associated with beneficial health outcomes. However, no study has separately examined the effects of multiple positive psychological constructs on behavioral, biological, and clinical outcomes after an acute coronary syndrome (ACS). Accordingly, we aimed to investigate associations of baseline optimism and gratitude with subsequent physical activity, prognostic biomarkers, and cardiac rehospitalizations in post-ACS patients. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 58 publications
6
68
0
1
Order By: Relevance
“…Our results also suggest that we should consider healthier behaviors (e.g., eating a healthier diet, engaging in more physical activity, etc. )-which are associated with many disease outcomes-not simply as potential confounders, especially in light of past research that showed that optimism is associated with increased physical activity, higher-quality sleep, abstention from cigarette smoking, and consumption of healthier diets (19,42,(46)(47)(48)(49). In the present study, given that assessments of optimism preceded assessments of behavior and that primary associations were somewhat attenuated after inclusion of behavior in the model, our findings might suggest that these behaviors partly serve as a mechanism underlying the observed associations between optimism and mortality (35, 36) (although we recognize that it may be difficult to distinguish well between confounding and intermediate variables and that health behaviors may be both confounding and intermediate variables).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that we should consider healthier behaviors (e.g., eating a healthier diet, engaging in more physical activity, etc. )-which are associated with many disease outcomes-not simply as potential confounders, especially in light of past research that showed that optimism is associated with increased physical activity, higher-quality sleep, abstention from cigarette smoking, and consumption of healthier diets (19,42,(46)(47)(48)(49). In the present study, given that assessments of optimism preceded assessments of behavior and that primary associations were somewhat attenuated after inclusion of behavior in the model, our findings might suggest that these behaviors partly serve as a mechanism underlying the observed associations between optimism and mortality (35, 36) (although we recognize that it may be difficult to distinguish well between confounding and intermediate variables and that health behaviors may be both confounding and intermediate variables).…”
Section: Discussionmentioning
confidence: 99%
“…The GQ-6 has been studied in a range of populations and used in clinical research projects (McCullough et al . 2002; Ivtzan & Papantoniou, 2014; Huffman et al . 2016a).…”
Section: Methodsmentioning
confidence: 99%
“…The GRACE study examined the impact of psychological constructs (e.g., optimism, gratitude) on subsequent outcomes (e.g., biomarkers, health behaviors, and rehospitalization) in patients with acute cardiac illness; methods and results have been described in detail elsewhere (Huffman et al, 2015a, Huffman et al, 2015b). …”
Section: Methodsmentioning
confidence: 99%